Supervised cardiac rehabilitation in patients with severe left ventricular dysfunction : Case series on functional and structural improvements - Pratiwi, Bunga Bella; Mayangsari, Veny (Universitas Brawijaya, 2026)
Background: Patients with coronary artery disease (CAD) frequently develop severe left ventricular (LV) dysfunction, which can lead to a worsening quality of life due to disease-related symptoms. Recently, cardiac rehabilitation (CR) has been recommended by international clinical guidelines to improve survival and functional recovery in these high-risk patients. Case Presentations: Two patients with CAD and heart failure with reduced ejection fraction (HFrEF) underwent supervised cardiac rehabilitation. First patient is a 43-year-old man with a left ventricular ejection fraction (LVEF) of 30% with risk factor as smoker and family history of heart disease, 6-minute walk test (6MWT) only 532 meters, VO2 max 19.94 mL/kg/min, and MET 5.69 has completed 89 sessions of cardiac rehabilitation (treadmill, calisthenics, and ergometer exercise). His 6MWT to 630 meters, VO₂ max improved to 22.58 mL/kg/min, and METs improved to 6.40. Before CR, the left ventricle (LV) was 7.5 cm long and had a biplane ejection fraction (EF) of 32%. After CR, structural improvements were found, increasing the LV length to 9.3 cm and the biplane EF to 58.4%. with improvements in execise capacity and symptoms. In Patient 2, a 50-year-old man with ST-elevation acute anterior myocardial syndrome (STEACS) (Killip I) with an LVEF of 20% with history of smoking and alcoholism, 6MWT 214 meters, VO2 mac 10.40 mL/kg/min, and MET 3.00 has completed 50 CR sessions ((treadmill, calisthenics, and ergometer exercise), demonstrating improvements in his 6MWT to 465 meters, VO₂ max to 17.93 mL/kg/min, and MET to 5.10. Echocardiography before CR found EF 20% and LV end-systolic volume index (LVESV) 20.7 ml and after eight months of rehabilitation showed improvement in EF to 47% and LVESV 53 ml with significant reduction in clinical symptoms. Conclusions: Supervised intensive cardiac rehabilitation resulted in functional and clinical improvements in high-risk CAD patients, including improved cardiac function in the context of heart failure. These findings demonstrate the important role of supervised rehabilitation programs in managing CAD patients with comorbid heart failure as the primary non-pharmacological management.